Recurrent breast abscess due to Salmonella paratyphi A:an unusual case - Ghadage, Dnyaneshwari P.; Wankhade, Archana B.; Mali, Rupali J.; Bhore, Arvind V. (International Journal of Research in Medical Sciences, 2017)
Bacterial mastitis is the most common variety of mastitis and is often caused by Staphylococcus aureus. Chronic mastitis is usually seen as a complication of tuberculosis & syphilis. A 31-year-old female presented with lump in the right breast for the past two years with pain for the past 15 days and discharge for the past two to three days. On examination, the lump was measured and was approximately 4x4 cm in size with a discharging sinus just lateral to the areola. No regional lymphadenopathy was noticed. A clinical diagnosis of “Lump in the right breast” with sinus probably due to tuberculosis was made. The lump had been excised surgically. Salmonella paratyphi A was isolated after repeated culture. She had responded to ceftriaxone, hence, unnecessary use of anti-tubercular drugs could be avoided. In chronic mastitis and breast abscess Salmonella species should be considered as one of the etiological agents.